Community structure of methanogenic archaea and methane production associated with compost-treated tropical rice-field soil - Singh A.; Singh R.S.; Upadhyay S.N.; Joshi C.G.; Tripathi A.K.; Dubey S.K. (My University, 2025)
The diversity and density of methanogenic archaea and methane production were investigated ex situ at different growth stages of rice plant cultivated in compost-treated tropical rice fields. The qPCR analysis revealed variation in methanogens population from 3.40 × 106 to 1.11 × 107 copies g-1 dws, in the year 2009 and 4.37 × 106 to 1.36 × 107 copies g-1 dws in the year 2010. Apart from methanogens, a large number of bacterial (9.60 × 109-1.44 × 1010 copies g-1 dws) and archaeal (7.13 × 107-3.02 × 108 copies g-1 dws) communities were also associated with methanogenesis. Methanogen population size varied in the order: flowering > ripening > tillering > postharvest > preplantation stage. The RFLP-based 16S rRNA gene-targeted phylogenetic analysis showed that clones were closely related to diverse group of methanogens comprising members of Methanomicrobiaceae, Methanosarcinaceae, Methanosaetaceae and RC I. Laboratory incubation studies revealed higher amount of cumulative CH4 at the flowering stage. The integration of methanogenic community structure and CH4 production potential of soil resulted in a better understanding of the dynamics of CH4 production in organically treated rice-field soil. The hypothesis that the stages of plant development influence the methanogenic community structure leading to temporal variation in the CH4 production has been successfully tested. © 2012 Federation of European Microbiological Societies.